Potency of Olorofim (F901318) Compared to Contemporary Antifungal Agents against Clinical Aspergillus fumigatus Isolates and Review of Azole Resistance Phenotype and Genotype Epidemiology in China - Su, Huilin (Antimicrob Agents Chemother, 2021)
Triazole resistance in Aspergillus fumigatus is an increasing worldwide problem that causes major challenges in the management of aspergillosis. New antifungal drugs are needed, with novel targets, that are effective in triazole-resistant infection. In this study, we retrospectively evaluated the potency of the novel drug olorofim compared to contemporary antifungal agents against 111 clinical A. fumigatus isolates collected from Huashan Hospital, Shanghai, China, using EUCAST methodology, and we reviewed the literature on triazole-resistant A. fumigatus (TRAF) published between 1966 and 2020 in China. Olorofim was active in vitro against all tested A. fumigatus isolates, with a MIC(90) of 0.031 mg/liter (range, 0.008 to 0.062 mg/liter). For 4 triazole-resistant A. fumigatus isolates, the olorofim MIC ranged between 0.016 and 0.062 mg/liter. The reported rates of TRAF in China are 2.5 to 5.56% for clinical isolates and 0 to 1.4% for environmental isolates. TR(34)/L98H/S297T/F495I is the predominant resistance mechanism, followed by TR(34)/L98H. Non-TR-mediated TRAF isolates, mostly harboring a cyp51A single point mutation, showed greater genetic diversity than TR-mediated resistant isolates. Resistance due to TR(34)/L98H and TR(34)/L98H/S297T/F495I mutations among TRAF isolates might have evolved from separate local isolates in China. Continuous isolation of TRAF in China underscores the need for systematic resistance surveillance as well as the need for novel drug targets, such as olorofim.